A&Y Racks - Abdul Samad, Ain Shalieyana; Ali Udin, Ali Khuraysha Alisia; Muslim, Nur Amalina; Suhainy, Nurul Haleeda; Abdul Karim, Nurizyan (2015)
A&Y is a shop who sells a unique rack located in a shopping mall named One Borneo, Sepanggar that allows the entire family to own their own personal rack in one convenient location as One Borneo as it is one of the famous shopping malls in Kota Kinabalu. A&Y produced a good and high quality of racks which is convenient for everyone. We produced different kind of styles in order to ensure everyone can use it, from kids to adults. While there are m'any shops that sell racks like A&Y, A&Y will excel due to its attention to detail regarding customers' satisfaction. Through unheralded customers' attention, A&Y will slowly but surely gain market share as our company emphasizes on the satisfaction of our customers. Lastly, our location will allow it to attract a lot of walk in traffic. People across Malaysia have decided to buy products from us when they want to fulfil their personal need, for example to have a good quality of racks. A&Y has seen this opportunity to produce the finest and highest quality of racks. This has shown that A&Y has the calibre to be one of the most successful racks seller in Malaysia. We, A&Y, saw the opportunity that this business has the potential of success provided that it is handled efficiently. People always need to have a product with a high quality in order to ease their life and to fulfil their need. Thus, A&Y sees this as a way to prosper in the market, by taking advantage of all these people need.